Oxford urdu silsila "Koonj" (for class 4) - Amna Azfar (Oxford University Press Oxford, 1999)
"Oxford Urdu Silsila Koonj" by Amna Azfar is a captivating collection of Urdu poetry that explores themes of love, loss, and introspection, beautifully woven into evocative verses that resonate with deep emotional expression.